Imagined communities reflections on the origin and spread of nationalism - Anderson, Benedict R. O'G. (Benedict Richard O'Gorman) 1936- (Verso, 2006)
'Imagined Communities' examines the creation & function of the 'imagined communities' of nationality & the way these communities were in part created by the growth of the nation-state, the interaction between capitalism & printing & the birth of vernacular languages in early modern Europe.